FORMING THE READINESS FOR PROFESSIONAL ACTIVITY AS A PEDAGOGICAL PROBLEM - Лузік, Е.; Акмалдінова, В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article deals with issues concerning theoretical and methodological fundamentals of forming the readiness for professional activity as a pedagogical problem, which involves the meaning readiness for professional activity, kinds of readiness, its structure, the professional activity essence and characteristics. Key competences of the future engineers in the field of air transport technologies. The ability of the education system to meet the demand of the individual and society for high-quality educational services determines the internal and spiritual development of the country. However, the solution of the problem of forming fundamentally new knowledge to implement it in the development of society, as well as further knowledge deepening and advancement is impossible without improving the mechanisms for developing and shaping innovative higher education policy. Insufficient conceptual formation of methodological bases and mechanisms of professional training of aviation transport specialists results in still more controversy regarding the objective demand for relevant specialists labor market, capable of perceiving new knowledge, new types and forms of activity, ready for continuous self-development and professional growth. The question of forming the engineering education specialization of future engineers in the field of air transport technologies is considered, which represents the basis of scientific thought in various areas of technical knowledge.